(untitled) (Analysis in Theory and Applications, 2020)
In this paper, we give four kinds of sharp estimates of two variants of bilinear Hausdorff operators on stratified groups, involving weighted Lebesgue spaces, classical Morrey spaces and central Morrey spaces. Meanwhile, some necessary and sufficient conditions of boundness are obtained.